KOORDINASI ANTARA PEJABAT PENYIDIK PEGAWAI NEGERI SIPIL DINAS KEHUTANAN DENGAN KEPOLISIAN DAERAH RIAU DAN KEJAKSAAN TINGGI RIAU DALAM MELAKUKAN PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN MENURUT UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN DI PROVINSI RIAU - SELVI SAFITRI; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Environmental crime happened a long time and occurs every year in Indonesia. In carrying out law enforcement in the field of the environment, especially in the forestry sector would not necessarily be carried out by the Indonesian National Police in view of the many obstacles encountered made the police should be assisted by the Civil Servant Investigators Forestry Service and the High Court of Riau that has been set in the contitution authorities between law enforcement agencies to coordinate and cooperate in the prevention and eradication of forest destruction.The purpose of this study was to determine the extent of coordination that has been by the Directorate of Special Criminal Riau Police, Civil Servant Investigators Forestry Service and the High Court of Riau in prevention and law enforcement in the forestry sector in accordance with Law Number 18 Year 2013 on the Prevention and Eradication of forest destruction, to determine obstacles in preventing and combating forest destruction, and to know the effort in overcoming dam prevention and eradication of forest destruction.This type of research is a sociological research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the Directorate of Special Crime, the Forest Service and the High Court of Riau.The prevention and destruction of forest law enforcement, law enforcement officers in the value is less coordination and lack of cooperation among law enforcement agencies. For that law enforcement officers are expected to further improve coordination in order to create its enforcement of the law especially those in the forestry sector.Keywords: Coordination-Law Enforcement-Forest destruction.